2020
DOI: 10.1021/acsaem.9b02021
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Multiple Effects of TiO2 Coating on NaMn0.33Fe0.33Ni0.33O2 Cathode Material for Na-Ion Batteries

Abstract: O3-type NaTMO2 (TM = transition metal) as cathodes for Na-ion batteries have aroused much interest. But the structural instability during charge–discharge cycles and the inferior rate capability restricts their application. In this study, we report a synergetic modification method to simultaneously increase the rate capacity and cycling stability of O3-type NaMn0.33Fe0.33Ni0.33O2(MFN) cathode material by integrating TiO2 coating and Ti4+ doping. Moreover, the synergetic mechanism has been put forward. First, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 52 publications
1
76
0
1
Order By: Relevance
“…189 The synergy of Ti 4+ doping and TiO 2 coating has also been reported for the O3-NaMn 0.33 Fe 0.33 Ni 0.33 O 2 composition. 213 The TiO 2 layer mitigates side reactions at the surface, while Ti 4+ doping enlarges the interslab spacing, facilitating sodium ion diffusion.…”
Section: Surface Coatingsmentioning
confidence: 99%
“…189 The synergy of Ti 4+ doping and TiO 2 coating has also been reported for the O3-NaMn 0.33 Fe 0.33 Ni 0.33 O 2 composition. 213 The TiO 2 layer mitigates side reactions at the surface, while Ti 4+ doping enlarges the interslab spacing, facilitating sodium ion diffusion.…”
Section: Surface Coatingsmentioning
confidence: 99%
“…The Al 2 O 3 coated Na[Ni 0.6 Co 0.2 Mn 0.2 ]O 2 cathode exhibited a high specific capacity of 151 mA h g −1 at 15 mA g −1 within the voltage range of 1.5–4.1 V, and delivered a high discharge capacity of approximately 115 mA h g −1 at a 1500 mA g −1 . The pouch-type full cell assembled from Al 2 O 3 coated Na[Ni 0.6 Co 0.2 Mn 0.2 ]O 2 /hard carbon exhibited a high energy density of 130 W h kg −1 and capacity retention of 75% after 300 cycles in the voltage range of 1.0–4.1 V. Yu et al 44 proposed that a synergetic modification method of TiO 2 coating and Ti 4+ doping not only suppressed the side reaction on the cathode surface, but also improved the structure stability and cycling performance of the layered structure. In addition, other research studies about AlF, 46 and AlPO 4, 147 for the surface coating on the layer oxide are reported; more effective coating strategies need to be explored in the future.…”
Section: O3-type Naxmn1−y−zfeycuzo2mentioning
confidence: 99%
“…In addition, the surface of the cathode material is modified to inhibit side reactions with the electrolyte and effectively delay the dissolution of the active material, which effectively improves the cycle stability, rate performance, and thermal stability of the material. 44–47…”
Section: Introductionmentioning
confidence: 99%
“…There are several good examples where the results from operando XRD has been used to improve the cyclability of a material by implementing small changes. For example by controlling the potential window or coating the materials [70,74,90] …”
Section: X‐ray Diffraction and Scatteringmentioning
confidence: 99%